Identification of potential artificial groundwater recharge sites in Mount Makiling Forest Reserve, Philippines using GIS and Analytical Hierarchy Process. (April 2019) - Sandoval, Janiella A.; Tiburan, Cristino L.
Abstract: Groundwater plays a critical role to the total water resource potential of the Philippines especially in areas where there is low rainfall and where surface water is not readily available for agriculture and domestic use. However, during the past decades, groundwater depletion and pollution have been evident in many parts of the Philippines. This has led to excessive groundwater extraction that resulted to the lowering of the groundwater at an alarming level. This problem was further aggravated by rapid urbanization in most parts of the country that drastically affected the natural recharge of the land. Hence, this study is aimed to identify potential sites for artificial groundwater recharge in selected watersheds of Mount Makiling Forest Reserve (MMFR) that can enhance sustainable yield and promote conservation and storage of excess water. It utilized several factors in identifying the artificial groundwater recharge sites. These include infiltration and percolation qualities (slope, soil, geology, geomorphology, land cover, aquifer transmissivity, drainage density, and lineaments), water quality (electrical conductivity), and water storability (depth to groundwater). Each factor was reclassified based on their potential for artificial groundwater recharge and was ranked based on their influence on groundwater movement using Analytical Hierarchy Process (AHP). The suitability scales used in the reclassification were very poor, poor, moderate, good, and very good. Seven specialists from various fields of study including engineering, hydrology, geology, and forestry contributed their knowledge on groundwater recharge through pair-wise comparison. The results of the AHP showed that aquifer transmissivity is the most important factor and is given a weight of 15.9%. On the other hand, soil is given the least importance with a weight of 7.5%. These results were used to process the final potential map which integrated all the thematic maps using weighted overlay. The results of the potential map showed that majority (83.97%) of the site is moderately suitable for artificial groundwater recharge. The good, moderate, and poor suitable sites have 2180.03 ha, 12, 274.39 ha, and 162.81 ha, respectively. Among the four watersheds in MMFR, Sipit Watershed has the largest cover of good suitable sites at 1288.68 ha or 59.11% of the entire study site. Meanwhile, the Tigbi Watershed has the least coverage of good sites with an approximate area of 54.46 ha only. In general, majority of these suitable sites for artificial groundwater recharge were found in sites that have high infiltration capacity and very acceptable water quality. It was also observed that the identified suitable sites were mainly located in cropland areas. Highlights: Aquifer transmissivity has the highest influence on artificial groundwater recharge. Meanwhile, soil has the least influence on artificial groundwater recharge. Majority of the study site was found to have moderately suitability. Sites with good suitability were located mostly in croplands areas. Injection wells will be the best option for recharge in these cropland areas.